Study of ice accretion and icing effects on aerodynamic characteristics of DU96 wind turbine blade profile - Jin, Jia Yi; Virk, Muhammad Shakeel (Cold regions science and technology, 2019)
In order to optimize the large wind turbines operation in ice prone cold regions, it is important to better understand the ice accretion physics and its effects on aerodynamic performance and power production losses. This paper describes a case study of ice accretion on DU96-W-180 airfoil, which has been used for large wind turbine blades such as NREL 5 MW. Analysis has been carried out for glaze and rime ice conditions using icing tunnel experimental data and multiphase Computational Fluid Dynamics (CFD) based numerical approach. Results show a difference in profile surface roughness and heat fluxes during rime and glaze ice accretion process, which leads to a significant change in rate and shape of ice accretion. More complex ice shapes are observed in case of glaze ice conditions that affects the aerodynamic performance differently from rime ice conditions. Numerical results are compared with the experimental data, where a good agreement is found. Results show higher aerodynamic performance degradation for glaze ice conditions particularly at higher angles of attack. •Wind turbine operations in icing conditions.•Atmospheric ice accretion on DU96 airfoil.•Aerodynamics performance.•Comparison of experimental and multiphase CFD numerical simulations.•Comparison of aerodynamic characteristics of clean and iced DU96 profiles.